Kesalahan Siswa SMK dalam Menyelesaikan Soal Program Linier Ditinjau dari Pemahaman Konseptual dan Prosedural - Dian Septi Nur Afifah; Basuki Sarjono; Lutfia Marsalina; Tomi Listiawan; Ika Mariana Putri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This research aims to describe the mistake of vocational student in solving linier program question in term of conceptual and procedural understanding. The research was conducted at SMKN I Boyolangu Tulungagung. Subject was chosen based on the highest number of mistakes when completing linier program question. Data collection techniques in this research are test and interview. The instruments used in this research were the main instrument and supporting instrument. The main instrument is the researcher itself, while the supporting instrument are the test sheet and interview guidelines. To test the data validity in this research used time triangulation. Data analysis based on indicator of conceptual and procedural understanding that include data reduction, data presentation and conclusion drawing. The result of this study indicate that students who make mistake do not have a good conceptual and procedural understanding. This can be seen from subject cannot explain how to solve the question. In addition, subject cannot continue the answer because subject do not know the next step that must be done. Subject alsocan not explain the steps in solving linier program question. For this reason, teacher need to pay attention to students’ understanding when learning in class, especially conceptual and procedural understanding. In addition, teacher mut choose or design a conceptual learning design and procedural understanding to achieve the learning objective.